Strategi Dakwah KHR. Ahmad Azaim Ibrahimy terhadap Abang Becak - As’ad As’ad; Mukhammad Baharun; Hanik Mufaridah (Fakultas Dakwah Universitas Ibrahimy, 2021)
In the current millennial era, there are so many da'wah activities, both directly and indirectly, whether they are digital-based or not. However, in particular, the kiai prefer to go directly to the field of da'wah, touch directly and interact directly. As for the da'wah carried out by KHR. Ahmad Azaim Ibrahimy to the becak brother whom most people underestimate in terms of social stratification. This article will describe the KHR propaganda strategy. Ahmad Azaim Ibrahimy against his brother becak in Sukorejo Situbondo. The research method used is a qualitative research method. The results show that KHR. Ahmad Azaim Ibrahimy uses three strategies used in preaching, namely hikmah, mauidhatil hasanah, and mujadalah. Mau'dhatul hasanah delivered by KHR. Ahmad Azaim Ibrahimy to the becak brother can be categorized into two principles, namely the principle of qoulan maisyuraa and the principle of qoulan layyina. Another strategy carried out by KHR. Ahmad Azaim Ibrahimy is advice, stories, criticism and instructions